Seleksi Pemimpin Nasional Melalui Proses Demokrasi - M Makhfudz (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: The condition of the country is currently experiencing a crisis of national leadership both in the hands of state administrators, government organizations and so on. Such conditions when viewed from the history of state administration in the era of the old order and the new order is no better than reform in terms of leaders who have noble ethical morals. This greatly influences the development of the country to advance in competition with other nations. So that the government continues to be preoccupied with revamping activities and regulating the implementation of the state so that it is clean from corruption and extortion which causes high costs. Then immediately take firm action after the Presidential Regulation number 87 of 2016 concerning the Establishment of the Clearing Task Force for Illegal Charges. Keywords: ethical morality, strategies to face obstacles. Abstrak: Kondisi Negeri kini sedang mengalami krisis kepemimpinan nasional baik melanda penyelenggara negara, organisasi pemerintahan dan lain sebagainya. Kondisi demikian jika dilihat dari sejarah penyelenggaraan negara di era orde lama dan orde baru tidak lebih baik ketimbang reformasi dari segi pemimpin yang memiliki moral etik yang luhur. Hal ini sangat mempengaruhi berkembangnya negara untuk maju menyaingi negara bangsa lainnya. Sehingga pemerintah terus disibukan oleh kegiatan pembenahan dan pengaturan strategi penyelenggaraan negara agar bersih dari korup dan pungli yang sebabkan biaya tinggi. Kemudian segera melakukan tindakan tegas pasca ditetapkan Perpres nomor 87 tahun 2016 tentang Pembentukan Satuan Tugas Sapu Bersih Pungli. Kata kunci: moral etik, strategi hadapi hambatan. DOI: 10.15408/sjsbs.v5i1.7901